Value of elastic strain ratio detection by transvaginal elastography in diagnosis of cervical carcinoma and judgment of illness - Xu-Sheng Zhang (Journal of Hainan Medical University, 2016)
Objective: To find the value of elastic strain ratio detection by transvaginal elastography in diagnosis of cervical carcinoma and judgment of illness. Methods: A total of 178 cases of women receiving vaginal ultrasound in our hospital from August 2011 to June 2014 were selected as research subjects, obtained cervical tissue block received pathological examination, and according to pathological results, all research subjects were divided into cervical carcinoma group 51 cases, benign cervical lesion group 78 cases and healthy control group 49 cases. Elastography pressure release index and elastic strain ratio, protein expression of CDK8, Ki-67, P53, Pin1 and Cyclin D1 in cervical tissue, serum tumor maker levels, serum COX-2, MMP-9, SCCAg, Apo-1/Fas and S-TK1 levels of all subjects were detected, and the correlation between elastic strain ratio and above cervical carcinoma-related indicator values was further analyzed. Results: Elastography pressure release index and elastic strain ratio of cervical carcinoma group were higher than those of benign cervical lesion group and healthy control group; protein expression levels of CDK8, Ki-67, P53, Pin1 and Cyclin D1 in cervical tissue of cervical carcinoma group were higher than those of benign cervical lesion group and healthy control group; serum CA125, Cyfra21-1, CA724 and CEA levels of cervical carcinoma group were higher than those of benign cervical lesion group and healthy control group; serum COX-2, MMP-9, SCCAg, Apo-1/Fas and S-TK1 levels of cervical carcinoma group were higher than those of benign cervical lesion group and healthy control group; elastic strain ratio had positive correlation with protein expression levels of CDK8, Ki-67, P53, Pin1 and Cyclin D1 in cervical tissue as well as CA125, Cyfra21-1, CA724, CEA, COX-2, MMP-9, SCCAg, Apo-1/Fas and S-TK1 levels in serum. Conclusion: Elastic strain ratio detected by transvaginal elastography can be used as the effective means for diagnosis of cervical carcinoma, and it has direct correlation with the severity of cervical carcinoma.